Cross-border regional development on the Bavarian-Czech border: The "right" forms of cooperation - Tobias Chilla; Luděk Fráně; Franziska Sielker; Jürgen Weber (Cross-border spatial development in Bavaria: Dynamics in cooperation - Potentials of integration, 2022)
The political dynamic in the Bavarian-Czech border area is still characterised and challenged by its location along the former Iron Curtain as well as its history of war and displacement. This particular situation has led to a unique pattern of cooperation. In comparison to other border areas it is striking that the middle level - i.e. the level between national and municipal cooperation - was only activated a few years ago. In the last five to ten years new developments have led to cooperation processes 'catching up'. We take this very interesting situation as a starting point for synoptic reflection. The analytical focus is on the two Euroregions in this space, on the European Region of Danube-Vltava, on the cross-border initiative of the European metropolitan region of Nuremberg, on the so-called development study of the regional development ministries and on the macro-regional strategy of the Danube region. These cooperation spaces and initiatives overlap and can be seen as reflecting institutional ambiguity. We developed our argument based on our personal involvement in the above-mentioned cooperation formats and conclude with an outlook concerning desirable future developments.
urn:nbn:de:0156-41580439; hdl:10419/253270; https://econpapers.repec.org/RePEc:zbw:arlabe:34
Keywords: 710; Cross-border cooperation; integration; governance; institutional ambiguity